CineCulture, Filmworks screen 'NO', May 10 - Uribes, Tom::::::::: (2013)
Fresno State's CineCulture program with Fresno Filmworks will screen a Best Foreign Language Academy Award nominated film from Chile, 'NO', 5:30 and 8:30 p.m. Friday, May 10, at the Tower Theatre